Response Hand Differentially Affects Action Word Processing - Heck, Nina; Mohr, Bettina (Frontiers in Psychology, 2017)
Recent approaches in the tradition of theories of semantic and conceptual “grounding” emphasize the role of perceptual and motor knowledge in language as well as action understanding. However, the role of the two cerebral hemispheres in integrating action-motor and language processes is not clear yet. The influence of a simultaneous motor tapping task on word processing was investigated in healthy participants. In a lexical decision task, uni-manual and bi-manual hand-related, as well as foot-related action verbs were presented in the left and right visual half-field. Group L performed tapping with the left hand and lexical decisions with their right hand. In Group R the reversed hand response pattern was applied. The results showed that the response hand had a strong influence on functional lateralization of word processing, when executed with the non-dominant hand in right handers. Projecting words to the ipsilateral hemisphere relative to the hemisphere performing lexical decisions, led to significantly decreased performance. Most interesting, the results showed that left hand responses led to an increased accuracy for hand-related in contrast to foot related action verbs. The findings suggest an influence of response hand on action word processing and can be interpreted on the basis of embodied cognition theory.